Characterization of T-cell immune responses in clinical trials of the candidate RTS, S malaria vaccine. Issue 1 (2nd January 2018) - Moris, Philippe; Jongert, Erik; van der Most, Robbert G.
ABSTRACT: The candidate malaria vaccine RTS, S has demonstrated 45.7% efficacy over 18 months against all clinical disease in a phase-III field study of African children. RTS, S targets the circumsporozoite protein (CSP), which is expressed on the Plasmodium sporozoite during the pre-erythrocyte stage of its life-cycle; the stage between mosquito bite and liver infection. Early in the development of RTS, S, it was recognized that CSP-specific cell-mediated immunity (CMI) was required to complement CSP-specific antibody-mediated immunity. In reviewing RTS, S clinical studies, associations between protection and various types of CMI (CSP-specific CD4 + T cells and INF-γ ELISPOTs) have been identified, but not consistently. It is plausible that certain CD4 + T cells support antibody responses or co-operate with other immune-cell types to potentially elicit protection. However, the identities of vaccine correlates of protection, implicating either CSP-specific antibodies or T cells remain elusive, suggesting that RTS, S clinical trials may benefit from additional immunogenicity analyses that can be informed by the results of controlled human malaria infection studies.